MORPHOANATOMICAL AND PHYTOCHEMICAL STUDIES FOR THE QUALITY CONTROL OF EUPHORBIA LANCIFOLIA SCHLTDL. (EUPHORBIACEAE - Paredes, M. E; Morales Coromac, R. E; Lima Ortiz, W. C; Valle Jurado, A. L.; Farchi, D; Prieto, J. M (university of el oued/جامعة الوادي, 2022)
Introduction: Euphorbia lancifolia Schltdl. (Euphorbiaceae) is a medicinal specie of central America origin, known as Ixbut in Guatemala, widely recognized for its important natural galactogogue activity. Methods: as identity test we here run macro and micro morphoanatomical studies of the characters of the vegetative organs. We also developed standard chemical tests for quality by both TLC and HPLC for infusions and tinctures of varying alcoholic strength. Their radical scavenging activities in DPPH and NO were also measured. Results: macro and micro morphoanatomical characters of the vegetative organs present a set of characteristics to facilitate the identification of dry powdered samples of this species. We developed optimal conditions for the TLC and HPLC phytochemical fingerprints of the 4 most common pharmacopoeial liquid herbal preparations from this herbal drug, namely infusion, 70%, 45% and 20% hydroalcoholic tinctures. Conclusions: Our work provides the Latin-American industry with a set of analyses to establish the identity and chemistry of E. lancifolia samples for quality control purposes.
Article
Keywords: HPLC; TLC; Microscopy; Macroscopy; Euphorbia lancifolia.